SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA PT. PERWIRA - Fitriani, Asa Febri Nur; Supriyanto, Edy (MEANS (Media Informasi Analisa dan Sistem), 2022)
Report recording system and product sales that have been carried out at PT. Officer is still manual by using the Microsoft Excel application which is done by the admin of PT. Officer which is considered very risky in data storage. In addition, if the customer comes directly to the store, the customer must wait at least 30 minutes for transaction processing because the admin is still processing it manually. With the creation of a Sales Information System at this Web-Based PT. Officer, it is hoped that it can help all parties to process the data. Data processing starts from the admin who can add products, edit products and delete products that are directly connected to the database. And customers can make product purchase transactions.This system was developed using Visual Studio Code, PHP, CSS, XAMP V3.3.0 and MYSQL applications. The method used or used in this information system is the Waterfall Method. With this website, transactions and sales reports can be processed in a structured manner and the security system can be guaranteed because it is stored in the database. This website is designed to assist customers in providing the desired product. The results of this information system can simplify the ordering process and the sales process. And this information system is also a means to expand and simplify services so that they can become faster, more effective and efficient.